Pengaruh Manajemen Modal Kerja terhadap Profitabilitas pada Industri Barang Konsumsi di Indonesia - Herman Sugisto; Juanda Juanda; Muhammad Basyir (Manajemen Inovasi Bisnis dan Strategi, 2023)
This study aims to determine the effect of working capital management including cash turnover, receivables turnover, and inventory turnover on profitability in the consumer goods industry of the food and beverage subsector listed on the Indonesia Stock Exchange (IDX). This study uses panel data with 30 food and beverage companies listed on the Indonesia Stock Exchange (IDX) from the period 2017-2021. The analysis method used is panel data regression analysis using Eviews 10. The sampling technique used was purposive sampling with multiple linear regression data analysis fixed effect model. The partial results showed that cash turnover, accounts receivable turnover and inventory turnover each had a positive and significant effect on profitability. The results of the study simultaneously show that Cash Turnover, Receivables Turnover and Inventory Turnover Affect Profitability in the Food and Beverage Subsector Consumer Goods Industry listed on the Indonesia Stock Exchange (IDX).